The nature of political alienation and electoral violence in Nigeria: A critical analysis of the 2019 general elections - God’stime Osariyekemwen Igiebor (Universitas Airlangga, 2022)
The Nigerian political system has experienced a high level of election-related violence at various epochs of its development. The incidences of violence during elections in Nigeria have resulted in the loss of lives and posed a threat to electoral participation and political stability. The study surveyed the perceptions of Nigerians on the effect of violence on the participation of eligible voters in the Nigerian electoral process. It attempts to ascertain the cause of the low turnout of voters in the 2019 general elections. The study adopted the survey research design and used data from 1,200 respondents selected from six local government areas representing the six geo-political zones. Simple percentages and Chi-Square statistical techniques were employed to test and determine the degree of association intrinsic to the stated hypotheses. The findings from the study show a positive relationship between violence and alienation. Thus, political violence perpetrated by political opponents and parties (among others) during elections results in the alienation of voters from the electoral process. Consequently, it is opined that the federal and state governments should put on modalities to mitigate the incidence of violence during elections. Also, perpetrators of electoral violence should be prosecuted and sanctioned accordingly.